2013
DOI: 10.1093/pubmed/fds104
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of parents' intention to limit children's television viewing

Abstract: Attitudes and normative pressure play an important role in determining parents' intention to limit their child's television viewing. The beliefs that were associated with parents' intention to limit should be emphasized by health professionals and in health communication campaigns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 31 publications
1
10
0
1
Order By: Relevance
“…The significant correlation between age and media viewing time is consistent with previous studies, which have reported this association in children aged <3 years and 3-16 years old [35,51,[62][63][64][65][66][67][68]. The current study also demonstrated a significant correlation between media viewing time and media preference level.…”
Section: Discussionsupporting
confidence: 92%
“…The significant correlation between age and media viewing time is consistent with previous studies, which have reported this association in children aged <3 years and 3-16 years old [35,51,[62][63][64][65][66][67][68]. The current study also demonstrated a significant correlation between media viewing time and media preference level.…”
Section: Discussionsupporting
confidence: 92%
“…This influence may come from parents role-modelling screen-viewing behaviours [ 23 , 26 29 ], the media equipment parents provide their children [ 23 , 28 ], parents’ attitudes to screen-viewing (e.g. belief it is a positive or negative behaviour) [ 28 , 30 ], and the rules or limits parents set on screen-viewing [ 23 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Further, it is unclear to what extent adults’ own screen time behaviour would determine their views on screen time restrictions for children. Finally, most previous research in this area has concentrated solely on parents [ 10 ]; however, many other adults who supervise children, such as grand-parents, aunts and uncles, friends and child care workers, also play an important role in limiting children’s screen time [ 11 ]. Hence, it is worth exploring this topic beyond the traditional parent–child relationship.…”
Section: Introductionmentioning
confidence: 99%